A method for preparing low-cost inorganic silicon-based aerogel
Through the sol-gel method of inorganic silicone source and bicarbonate solvent replacement, combined with the atmospheric drying process, the problems of long preparation cycle and poor performance of SiO2 aerogel are solved, and low-cost and high-performance SiO2 aerogel preparation is achieved. , suitable for thermal insulation materials.
Patent Information
- Application Number
- CN202310298489.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-24
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-03-24
AI Technical Summary
The preparation period of SiO2 aerogels prepared by inorganic silicone source at normal pressure drying is long and cumbersome, and the material network structure is not easy to regulate, resulting in a large gap in material performance, high cost and low industrialization rate.
Using a low-cost inorganic silicone source as raw material, it is replaced by sol-gel method and bicarbonate solvent, and dried at normal pressure to obtain a hydrophobic SiO2 aerogel, with a three-dimensional nanoporous network structure, shortening the preparation cycle and reducing costs. Improve industrialization efficiency.
A low-cost, high-performance inorganic silicone source SiO2 aerogel comparable to the silicone source preparation performance, has high specific surface area, low density, low thermal conductivity, good thermal stability and chemical stability, and is suitable as a thermal insulation material .
Smart Images

Figure CN116375042B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation technology of nano porous materials and relates to a method for preparing low-cost inorganic silicon-based aerogel. Background Art
[0002] Aerogel is a magical material that changes the world and is listed as one of the top ten hot new materials in the 21st century! It is a porous amorphous solid material with a three-dimensional nano-skeleton structure composed of polymer molecular chains or nanoparticles. It has structural characteristics such as low density, high pore volume, high porosity and large specific surface area. Its performance is extremely excellent and it has maintained 14 world records. It is the best thermal insulation material so far. It has extensive research significance and application value in military and civilian fields such as aerospace, petrochemicals, shipping, building insulation, battery insulation, cold chain logistics, and cold-proof fabrics.
[0003] Among them, SiO 2 Aerogel has been developed for more than 90 years since it was first invented by American scientist Kistler.S. in 1931. 2 The research and application of aerogels have expanded from the earliest defense and military fields to aerospace, building insulation and many other military and civilian fields. 2 Aerogels and their composite materials have been favored by many industries due to their unique properties, but their use is limited due to high raw material costs and manufacturing expenses, which has become a pain point in the industry. Aspen Aerogels data shows that SiO 2 Aerogel material costs account for about 48% of the total cost, and manufacturing costs account for about 44%. 2 The production cost of aerogel is mainly concentrated in silicon source (raw material), equipment depreciation (drying) and energy consumption (drying). 2 The preparation process of aerogel first requires SiO 2Gel, and then the gas is replaced by the liquid phase in the gel by drying to form aerogel. At present, there are two kinds of raw materials for production. One is inorganic silicon source, including water glass (sodium silicate) and silicon tetrachloride, and the other is organic silicon source, including functional silanes such as methyl orthosilicate (TMOS, also known as tetramethoxysilane) and ethyl orthosilicate (TEOS, also known as tetraethoxysilane). Among them, the organic silicon source has high purity and good process adaptability, and can be adapted to supercritical drying and atmospheric drying processes, but the defect of organic silicon element as a raw material is high price. At present, domestic and foreign enterprises using supercritical drying process basically use organic silicon source. Inorganic silicon source is relatively cheaper, but it has been used less for a long time. On the one hand, because inorganic silicon source can only be applied to atmospheric drying technology, the atmospheric method is still immature; on the other hand, in the preparation process of aerogel with water glass as silicon source, a large amount of water is needed to wash the sodium salt in the gel, and the aqueous solution of sodium salt is difficult to separate, resulting in a large amount of wastewater that is difficult to treat. Improper treatment may cause large areas of land salinization. Therefore, the most mainstream industrial production route at home and abroad is the production process of orthosilicate as raw material combined with supercritical drying process. Based on the most mainstream industrial production route at home and abroad, the cost reduction of aerogel mainly starts from the raw material cost and drying cost. By using low-cost inorganic silicon source combined with atmospheric pressure drying to replace the high-cost organic silicon source combined with supercritical preparation process, the preparation cycle is greatly reduced, the investment recovery period is shortened, and the manufacturing cost is greatly reduced. The inorganic silicon source system combined with atmospheric pressure drying preparation process has broad development prospects.
[0004] At present, many scholars at home and abroad have devoted themselves to the research of inorganic silicon source system combined with atmospheric pressure drying preparation process. In 2016, Tongji University used water glass as raw material, and prepared SiO2 by sol-gel method, ethanol solvent exchange / hexamethyldisilazane / trimethylchlorosilane surface modification and freeze drying in water system. 2 Aerogel powder. The material density is 168kg / m 3 , with a specific surface area of 280m 2 / g, and the preparation cycle is greater than 130h. In 2018, the University of Leuven in Belgium used water glass as raw material, and prepared SiO2 by sol-gel method, surface modification of n-hexane / trimethylsilyl chloride / isopropanol solution and atmospheric pressure drying in an alcohol / water system. 2 Aerogel powder. The density of this material is 132kg / m 3 , thermal conductivity is 0.0254W / (m·K), and the preparation cycle is greater than 45h. In 2019, Wuhan University of Technology used water glass as raw material, and prepared SiO2 by sol-gel method, hexamethyldisilazane / trimethylchlorosilane surface modification and atmospheric pressure drying in an alcohol / water system. 2 Aerogel powder. The density of this material is 121kg / m 3, thermal conductivity is 0.0245W / (m·K), and the preparation cycle is greater than 50h. In 2020, the Swiss Federal Laboratory for Materials Science used water glass as raw material, and used the sol-gel method, ethanol, n-hexane and other phase transfer catalysts and atmospheric pressure drying in an organic solvent / water system to prepare SiO 2 Aerogel powder. The tap density of this material is 83kg / m 3 , the preparation cycle is greater than 60h. In 2022, Changzhou University used water glass as raw material, and prepared silica aerogel powder in an alcohol / water system using the sol-gel method, hexamethyldisilazane and heptane solvent exchange / surface modification and atmospheric pressure drying. The material density is 180kg / m 3 , thermal conductivity is 0.033W / (m·K), and the preparation cycle is greater than 48h.
[0005] By reviewing and summarizing the literature of the past decade, it is found that the current preparation methods have the following disadvantages: First, the material preparation cycle is long and cumbersome. For water glass inorganic silicon source, most of them are dried at normal pressure, but the premise is that sodium salt needs to be washed out by a large amount of water, and the surface tension is weakened by complex silane surface modification, which leads to a long and cumbersome preparation cycle, a large amount of organic solvent consumption, and the preparation cost reduction is not obvious. Second, the material network structure is not easy to control. For water glass and other inorganic silicon sources / water systems, the hydrolysis rate is extremely fast, the formed silanol reaction activity is very large, and the condensation agglomeration leads to extremely poor formability. The microscopic performance is agglomerated particles. The network construction and preparation process are not easy to control. The SiO 2 Aerogels are all powders. Third, there is a large gap in material performance. For SiO2 produced by combining inorganic silicon sources such as water glass with silane surface modification and atmospheric pressure drying, 2 Aerogel has poor three-dimensional network formability due to condensation and agglomeration, resulting in high density and high thermal conductivity, and the material has no advantages in research and application. 2 There are still many technical difficulties in the aerogel process route. It is necessary to find a reasonable preparation method and develop a low-cost inorganic silicon-based aerogel and its rapid preparation method to solve the problems found so far and realize SiO 2 Aerogel is created at low cost and is SiO 2 It provides solutions and references for solving the problems faced by aerogel research and industrialization, such as high cost and low industrialization rate. Summary of the invention
[0006] The present invention aims to solve the problem of preparing SiO by drying inorganic silicon source at normal pressure. 2 The existing aerogel technology has the following technical problems: long and complicated material preparation cycle, difficult material network structure regulation, and large gap in material performance. The purpose of the present invention is to develop a low-cost method for preparing inorganic silicon-based aerogels, form a process route, and obtain a SiO2 aerogel that can be prepared with an organic silicon source. 2Aerogel performance is comparable to low-cost high-performance inorganic silicon source SiO 2 Aerogel, SiO 2 It provides solutions and references for solving the problems faced by aerogel research and industrialization, such as long preparation cycle, high cost, and low industrialization rate.
[0007] In order to solve the above technical problems, the technical solution of the present invention is: using a low-cost inorganic silicon source as a raw material and deionized water as a solvent, a sol-gel method, bicarbonate solvent replacement, and normal pressure drying to obtain a hydrophobic SiO 2 Aerogel, a material with a three-dimensional nanoporous network structure, is more 2 The aerogel method not only shortens the preparation cycle, reduces costs, but also improves industrial efficiency. 2 Aerogel products, the SiO 2 Aerogel also has excellent properties such as high specific surface area, low density, high hydrophobicity, and low thermal conductivity. It also has good thermal stability, chemical stability, and structural stability. Its high specific surface area gives it good thermal insulation and high temperature resistance, so it is an ideal thermal insulation material. 2 The density of aerogel is 63-125kg / m 3 , thermal conductivity is 0.024-0.03W / (m·K), water contact angle is 150°-156°, specific surface area is 560-603m 2 / g, the average pore size is 15-26nm, and the preparation cycle is 35-49h.
[0008] The specific technical solution of the present invention is: a method for preparing low-cost inorganic silicon-based aerogel, and the specific steps are as follows:
[0009] (1)SiO 2 Preparation of sol and wet gel
[0010] A certain amount of hydrophobic modifier is measured and poured into a container, deionized water is added, and the magnetic stirring speed is adjusted to stir until dissolved to obtain a transparent solution; while continuing to stir, a certain volume of inorganic silicon source reagent is measured and added to the above transparent solution, and stirred evenly to obtain a mixed solution; the speed of the magnetic stirrer is adjusted again, and an acid catalyst is quickly added to adjust the pH of the above mixed solution, and after stirring evenly at room temperature, the mixed solution is allowed to stand for gelation to obtain SiO 2 Wet gel;
[0011] (2)SiO 2 Solvent replacement of wet gels
[0012] At a certain temperature, the SiO 2A deionized aqueous solution of bicarbonate was added to the wet gel to replace the solvent. 2 The wet gel was taken out and the organic solvent solution of functional silane was used for solvent replacement. 2 The wet gel was taken out and placed in the corresponding organic solvent. 2 The wet gel is left to dry;
[0013] (3)SiO 2 Drying of wet gel
[0014] After replacing the solvent in step (2), SiO 2 After the wet gel is placed at a certain temperature and dried under normal pressure, the hydrophobic inorganic silicon-based SiO 2 Aerogel.
[0015] Preferably, the inorganic silicon source reagent in step (1) is a sodium silicate solution or a potassium silicate solution; the density of the sodium silicate solution or the potassium silicate solution is 1.36-1.4 g / cm 3 , where SiO 2 The mass fraction of the hydrophobic modifier is 26%-32%; the hydrophobic modifier described in step (1) is one of sodium methyl silicate or potassium methyl silicate; the molar ratio of the inorganic silicon source reagent to the hydrophobic modifier is (0.5-2.9):1; the volume ratio of the added deionized water to the inorganic silicon source reagent described in step (1) is (5-17):1.
[0016] Preferably, in step (1), the rotation speed of the magnetic stirring is adjusted to 300-400 r / min, and the rotation speed of the magnetic stirring is adjusted again to 700-900 r / min.
[0017] Preferably, the acidic catalyst in step (1) is one of acetic acid, propionic acid or oxalic acid.
[0018] Preferably, the time for adding the acidic catalyst in step (1) is controlled within 5-8 seconds; and the pH value of the mixed solution is adjusted to 6-7.5.
[0019] Preferably, the deionized aqueous solution of bicarbonate described in step (2) is an aqueous solution of ammonium bicarbonate or an aqueous solution of sodium bicarbonate; the molar solubility of the bicarbonate is 0.41-0.53 mol / L; and the time for solvent replacement with the deionized aqueous solution of bicarbonate is 12-15 h.
[0020] Preferably, the functional silane in the organic solvent solution of the functional silane in step (2) is one of dimethylchlorosilane and trimethylchlorosilane; the organic solvent is one of ethanol, methanol or isopropanol; the volume concentration of the organic solvent solution of the functional silane is 3.5%-6.2%; and the replacement time is 7.5-11h.
[0021] Preferably, the corresponding organic solvent described in step (2) refers to the organic solvent used in the organic solvent of the functional silane, and the time for solvent replacement of the corresponding organic solvent is 6-10 hours.
[0022] Preferably, the certain temperature in step (2) is 25-35°C.
[0023] Preferably, the normal pressure drying temperature in step (3) is 60-85° C.; the normal pressure drying time in step (3) is 8-12 h.
[0024] Beneficial effects:
[0025] (1) Compared with SiO prepared by organic silicon source combined with supercritical drying 2 Aerogel, the present invention prepares SiO 2 Aerogel still has excellent properties such as high specific surface area, low density, high hydrophobicity and low thermal conductivity.
[0026] (2) Compared with the traditional atmospheric pressure drying method to prepare SiO 2 The process of aerogel can produce SiO in a short period of time. 2 The aerogel produced has good stability, and the preparation method is based on CO 2 The pore structure of the wet gel is strengthened and stabilized instead of the traditional method of chemical grafting modification, thus avoiding the large-scale use of organic solvents and reducing costs, which is expected to be industrially feasible.
[0027] (3) Compared with the traditional atmospheric pressure drying method to prepare SiO 2 The process of aerogel is to compound hydrophobic modifiers such as sodium methyl silicate on the basis of inorganic silicon source, and prepare hydrophobic SiO 2 In addition, the presence of hydrophobic modifiers such as sodium methyl silicate also increases the steric hindrance effect, avoiding the rapid hydrolysis and condensation of the inorganic silicon source, and solving the problem of SiO 2 The technical difficulty of controlling the network structure during the preparation of aerogels. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The inorganic silicon source SiO prepared in Example 1 2 Macroscopic sample image of aerogel;
[0029] Figure 2 The inorganic silicon source SiO prepared in Example 1 2 Aerogel pore size distribution diagram;
[0030] Figure 3 The inorganic silicon source SiO prepared in Example 1 2Contact angle test diagram of aerogel;
[0031] Figure 4 The inorganic silicon source SiO prepared in Example 1 2 Microstructure of aerogel. DETAILED DESCRIPTION
[0032] The present invention is further described below with reference to examples, but the protection scope is not limited thereto.
[0033] Example 1
[0034] Measure 0.0533 mol of sodium methyl silicate and pour it into a container. Add 30 mL of deionized water and adjust the magnetic stirring speed to 320 r / min. Stir until the sodium methyl silicate is dissolved to obtain a transparent solution. While continuing to stir, measure 5 mL of a 1.36 g / cm 3 、SiO 2 A sodium silicate solution (0.0309 mol) with a mass fraction of 27.3% was added to the above transparent solution and stirred to obtain a mixed solution. The speed of the magnetic stirrer was adjusted to 756 r / min, and the acetic acid catalyst was added to the mixed solution just after 5 seconds. The pH of the mixed solution was adjusted to 6.1, stirred at room temperature, and then allowed to stand to gel to obtain SiO 2 Wet gel. At 25°C, take 200 mL of 0.42 mol / L sodium bicarbonate aqueous solution and 2 The wet gel was subjected to solvent replacement for 12 h. After this step, the SiO 2 The wet gel was taken out and the solvent was replaced with 3.7% trimethylsilyl chloride in anhydrous ethanol solution for 7.8 h. After this step, SiO 2 The wet gel was taken out and replaced with anhydrous ethanol for 6 hours. This is the end of the solvent replacement process. 2 The wet gel is waiting to be dried. After the solvent replacement process is completed, SiO 2 The wet gel was placed at 64 °C and dried at normal pressure for 9 h to obtain a hydrophobic inorganic silicon-based SiO 2 Aerogel. The SiO 2 The density of aerogel is 121kg / m 3 , thermal conductivity is 0.0203W / (m·K), water contact angle is 152°, specific surface area is 603m 2 / g, the average pore size is 15nm, and the preparation cycle is 35.3h. 2 The macroscopic sample image, pore size distribution image, contact angle test image, and microstructure image of the aerogel are shown in Figure 1. Figure 1 , Figure 2 , Figure 3 , Figure 4 As shown. Figure 1 It can be seen intuitively that the material has SiO 2 The unique "blue smoke" effect of aerogel indicates that SiO 2 Aerogel; Figure 2 The SiO prepared by this method is obtained 2 The pore size distribution of aerogels is wide, but mainly mesopores, with pore sizes mainly distributed around 15nm, and a uniform pore structure, which also ensures its low thermal conductivity and low density performance; Figure 3 It was verified that the aerogel has superhydrophobic properties; Figure 4 It was demonstrated that the aerogel had a uniform three-dimensional network porous structure.
[0035] Example 2
[0036] Measure 0.071 mol of sodium methyl silicate and pour it into the container. Add 81 mL of deionized water and adjust the magnetic stirring speed to 348 r / min. Stir until the sodium methyl silicate is dissolved to obtain a transparent solution. While continuing to stir, measure 9 mL of a 1.38 g / cm 3 、SiO 2 A potassium silicate solution (0.059 mol) with a mass fraction of 28.7% was added to the above transparent solution and stirred to obtain a mixed solution. The speed of the magnetic stirrer was adjusted to 808 r / min, and the propionic acid catalyst was added to the mixed solution just after 6 seconds. The pH of the mixed solution was adjusted to 6.7, stirred at room temperature, and then allowed to stand to gel to obtain SiO 2 Wet gel. At 28°C, measure 300 mL of 0.45 mol / L ammonium bicarbonate aqueous solution and 2 The wet gel was subjected to solvent replacement for 13.1 h. After this step, the SiO 2 The wet gel was taken out and solvent replacement was continued for 8.6 h using a methanol solution of dimethylchlorosilane with a volume fraction of 4.1%. After this step was completed, SiO 2 The wet gel was taken out and replaced with methanol for 7.6 hours. This was the end of the solvent replacement process. 2 The wet gel is waiting to be dried. After the solvent replacement process is completed, SiO 2 The wet gel was placed at 69 °C and dried at normal pressure for 9.8 h to obtain a hydrophobic inorganic silicon-based SiO 2 Aerogel. The SiO 2 The density of aerogel is 92kg / m 3 , thermal conductivity is 0.0218W / (m·K), water contact angle is 150.4°, specific surface area is 592m 2 / g, the average pore size is 16.6nm, and the preparation cycle is 39.6h.
[0037] Example 3
[0038] Measure 0.067 mol of potassium methyl silicate and pour it into the container. Add 143 mL of deionized water and adjust the magnetic stirring speed to 366 r / min. Stir until the potassium methyl silicate is dissolved to obtain a transparent solution. While continuing to stir, measure 11 mL of a solution with a density of 1.392 g / cm 3 、SiO 2 A sodium silicate solution (0.075 mol) with a mass fraction of 29.6% was added to the above transparent solution and stirred to obtain a mixed solution. The speed of the magnetic stirrer was adjusted to 831 r / min, and the oxalic acid catalyst was added to the mixed solution at 7 s. The pH of the mixed solution was adjusted to 6.5, stirred at room temperature, and then allowed to stand to gel to obtain SiO 2 Wet gel. At 30°C, measure 370 mL of 0.49 mol / L sodium bicarbonate aqueous solution to SiO 2 The wet gel was subjected to solvent replacement for 12.3 h. After this step, the SiO 2 The wet gel was taken out and the solvent was replaced with 5.35% trimethylsilyl chloride isopropanol solution for 7.5 h. After this step, SiO 2 The wet gel was taken out and replaced with isopropanol for 8.3 hours. This was the end of the solvent replacement process. 2 The wet gel is waiting to be dried. After the solvent replacement process is completed, SiO 2 The wet gel was placed at 77 °C and dried at normal pressure for 8 h to obtain a hydrophobic inorganic silicon-based SiO 2 Aerogel. The SiO 2 The density of aerogel is 72kg / m 3 , thermal conductivity is 0.0257W / (m·K), water contact angle is 155.1°, specific surface area is 568m 2 / g, the average pore size is 24.6nm, and the preparation cycle is 36.6h.
[0039] Example 4
[0040] Measure 0.038 mol of sodium methyl silicate and pour it into a container. Add 136 mL of deionized water and adjust the magnetic stirring speed to 375 r / min. Stir until the sodium methyl silicate is dissolved to obtain a transparent solution. While continuing to stir, measure 8 mL of a 1.4 g / cm 3 、SiO 2A 29% potassium silicate solution (0.054 mol) was added to the transparent solution and stirred to obtain a mixed solution. The speed of the magnetic stirrer was adjusted to 862 r / min, and the oxalic acid catalyst was added to the mixed solution at 8 s. The pH of the mixed solution was adjusted to 6, stirred at room temperature, and then allowed to stand to gel to obtain SiO 2 Wet gel. At 30°C, 375 mL of 0.52 mol / L ammonium bicarbonate aqueous solution was taken to SiO 2 The wet gel was subjected to solvent replacement for 14.4 h. After this step, the SiO 2 The wet gel was taken out and the solvent was replaced with anhydrous ethanol solution of trimethylchlorosilane with a volume fraction of 5.78% for 9.5 hours. After this step, SiO 2 The wet gel was taken out and replaced with anhydrous ethanol for 8.9 hours. This was the end of the solvent replacement process. 2 The wet gel is waiting to be dried. After the solvent replacement process is completed, SiO 2 The wet gel was placed at 80 °C and dried at normal pressure for 10.7 h to obtain a hydrophobic inorganic silicon-based SiO 2 Aerogel. The SiO 2 The density of aerogel is 76.4kg / m 3 , thermal conductivity is 0.0246W / (m·K), water contact angle is 154.8°, and specific surface area is 577.5m 2 / g, the average pore size is 22.1nm, and the preparation cycle is 44h.
[0041] Example 5
[0042] Measure 0.029 mol of sodium methyl silicate and pour it into a container. Add 124 mL of deionized water and adjust the magnetic stirring speed to 389 r / min. Stir until the sodium methyl silicate is dissolved to obtain a transparent solution. While continuing to stir, measure 8 mL of a solution with a density of 1.375 g / cm 3 、SiO 2 A 30% sodium silicate solution (0.055 mol) was added to the transparent solution and stirred to obtain a mixed solution. The speed of the magnetic stirrer was adjusted to 893 r / min, and the acetic acid catalyst was added to the mixed solution in 6 seconds. The pH of the mixed solution was adjusted to 6.7, stirred at room temperature, and then allowed to stand to gel to obtain SiO 2 Wet gel. At 33°C, 355 mL of 0.42 mol / L sodium bicarbonate aqueous solution was taken to SiO 2 The wet gel was subjected to solvent replacement for 15 h. After this step, the SiO 2The wet gel was taken out and solvent replacement was continued for 10.4 h using a methanol solution of dimethylchlorosilane with a volume fraction of 6.2%. After this step was completed, SiO 2 The wet gel was taken out and replaced with methanol for 9.7 hours. This was the end of the solvent replacement process. 2 The wet gel is waiting to be dried. After the solvent replacement process is completed, SiO 2 The wet gel was placed at 84 °C and dried at normal pressure for 11.6 h to obtain a hydrophobic inorganic silicon-based SiO 2 Aerogel. The SiO 2 The density of aerogel is 84.7kg / m 3 , thermal conductivity is 0.0231W / (m·K), water contact angle is 153.6°, specific surface area is 588.7m 2 / g, the average pore size is 19.9nm, and the preparation cycle is 47.2h.
[0043] Example 6
[0044] Measure 0.015 mol of potassium methyl silicate and pour it into a container. Add 60 mL of deionized water and adjust the magnetic stirring speed to 400 r / min. Stir until the potassium methyl silicate is dissolved to obtain a transparent solution. While continuing to stir, measure 5 mL of a 1.38 g / cm 3 、SiO 2 A 31% potassium silicate solution (0.036 mol) was added to the transparent solution and stirred to obtain a mixed solution. The speed of the magnetic stirrer was adjusted to 725 r / min, and the propionic acid catalyst was added to the mixed solution at 7 s. The pH of the mixed solution was adjusted to 7.2, stirred at room temperature, and allowed to stand to gel to obtain SiO 2 Wet gel. At 35°C, take 240 mL of 0.44 mol / L ammonium bicarbonate aqueous solution and 2 The wet gel was subjected to solvent replacement for 12 h. After this step, the SiO 2 The wet gel was taken out and the solvent was replaced with 5.5% trimethylsilyl chloride isopropanol solution for 7.8 h. After this step, SiO 2 The wet gel was taken out and replaced with isopropanol for 8.7 hours. This was the end of the solvent replacement process. 2 The wet gel is waiting to be dried. After the solvent replacement process is completed, SiO 2 The wet gel was placed at 60°C and dried at normal pressure for 9.5 h to obtain a hydrophobic inorganic silicon-based SiO 2 Aerogel. The SiO 2 The density of aerogel is 109.3kg / m 3, thermal conductivity is 0.0265W / (m·K), water contact angle is 153.4°, and specific surface area is 597.4m 2 / g, the average pore size is 18.7nm, and the preparation cycle is 38.5h.
[0045] Example 7
[0046] Measure 0.024 mol of potassium methyl silicate and pour it into the container. Add 161.5 mL of deionized water and adjust the magnetic stirring speed to 300 r / min. Stir until the potassium methyl silicate is dissolved to obtain a transparent solution. While continuing to stir, measure 9.5 mL of a 1.37 g / cm 3 、SiO 2 A sodium silicate solution (0.069 mol) with a mass fraction of 31.8% was added to the above transparent solution and stirred to obtain a mixed solution. The speed of the magnetic stirrer was adjusted to 780 r / min, and the propionic acid catalyst was added to the mixed solution just after 8 s. The pH of the mixed solution was adjusted to 7.5, stirred at room temperature, and then allowed to stand to gel to obtain SiO 2 Wet gel. At 25°C, measure 370 mL of 0.53 mol / L sodium bicarbonate aqueous solution to SiO 2 The wet gel was subjected to solvent replacement for 15 h. After this step, the SiO 2 The wet gel was taken out and the solvent was replaced with a methanol solution of dimethylchlorosilane with a volume fraction of 5.5% for 11 hours. After this step, SiO 2 The wet gel was taken out and replaced with methanol for 10 h. This was the end of the solvent replacement process. 2 The wet gel is waiting to be dried. After the solvent replacement process is completed, SiO 2 The wet gel was placed at 85 °C and dried under normal pressure for 12 h to obtain a hydrophobic inorganic silicon-based SiO 2 Aerogel. The SiO 2 The density of aerogel is 65.3kg / m 3 , thermal conductivity is 0.0275W / (m·K), water contact angle is 156°, specific surface area is 562m 2 / g, the average pore size is 25.4nm, and the preparation cycle is 48.5h.
Claims
1. A method for preparing a low-cost inorganic silicon-based aerogel, the specific steps of which are as follows: (1) Preparation of SiO2 sol and wet gel A certain amount of hydrophobic modifier is measured and poured into a container, deionized water is added, and the magnetic stirring speed is adjusted to stir until dissolved to obtain a transparent solution; while continuing to stir, a certain volume of inorganic silicon source reagent is measured and added to the above transparent solution, and stirred evenly to obtain a mixed solution; The speed of the magnetic stirrer is adjusted again, and an acidic catalyst is added to adjust the pH of the mixed solution. After stirring evenly, the mixed solution is allowed to stand to gel, thereby obtaining a SiO2 wet gel. The speed of magnetic stirring is adjusted to 300-400 r / min, and the speed of magnetic stirring is adjusted to 700-900 r / min again; the time of adding the acid catalyst is controlled to be 5-8 s; the pH value of the mixed solution is adjusted to 6-7.5; (2) Solvent replacement of SiO2 wet gel At a certain temperature, a deionized aqueous solution of bicarbonate is added to the SiO2 wet gel obtained in step (1) to perform solvent replacement, then the SiO2 wet gel is taken out, and the organic solvent solution of functional silane is used to perform solvent replacement, then the SiO2 wet gel is taken out again, and the corresponding organic solvent is used to place the SiO2 wet gel, and the SiO2 wet gel is left to dry; (3) Drying of SiO2 wet gel The SiO2 wet gel obtained after solvent replacement in step (2) is placed at a certain temperature and dried at normal pressure to obtain a hydrophobic inorganic silicon-based SiO2 aerogel.
2. The preparation method according to claim 1, characterized in that The inorganic silicon source reagent described in step (1) is one of sodium silicate solution or potassium silicate solution; the density of sodium silicate solution or potassium silicate solution is 1.36-1.4g / cm 3 , wherein the mass fraction of SiO2 is 26%-32%; the hydrophobic modifier described in step (1) is one of sodium methyl silicate or potassium methyl silicate; the molar ratio of the inorganic silicon source reagent to the hydrophobic modifier is (0.5-2.9):1; the volume ratio of the added deionized water to the inorganic silicon source reagent described in step (1) is (5-17):
1.
3. The preparation method according to claim 1, characterized in that The acidic catalyst described in step (1) is one of acetic acid, propionic acid or oxalic acid.
4. The preparation method according to claim 1, characterized in that The deionized aqueous solution of bicarbonate described in step (2) is an aqueous solution of ammonium bicarbonate or an aqueous solution of sodium bicarbonate; the molar solubility of the bicarbonate is 0.41-0.53 mol / L; and the time for solvent replacement with the deionized aqueous solution of bicarbonate is 12-15 hours.
5. The preparation method according to claim 1, characterized in that The functional silane in the organic solvent solution of the functional silane described in step (2) is one of dimethylchlorosilane and trimethylchlorosilane; the organic solvent is one of ethanol, methanol or isopropanol; the volume concentration of the organic solvent solution of the functional silane is 3.5%-6.2%; and the replacement time is 7.5-11h.
6. The preparation method according to claim 1, characterized in that The corresponding organic solvent described in step (2) refers to the organic solvent used in the organic solvent of the functional silane, and the time for the solvent replacement of the corresponding organic solvent is 6-10 hours.
7. The preparation method according to claim 1, characterized in that The certain temperature described in step (2) is 25-35°C.
8. The preparation method according to claim 1, characterized in that The normal pressure drying temperature in step (3) is 60-85° C.; the normal pressure drying time in step (3) is 8-12 hours.